Heritage education in history teaching: a transformation of historical consciousness: Heritage education in history teaching: a transformation of historical consciousness (Revista de História da UEG (REVHIST), 2025)
This article analyzes how heritage education, integrated with history teaching, influences the historical awareness of students in the municipality of Raposa, Maranhão. A qualitative approach was adopted in a case study conducted with classes at the Jarbas Passarinho School, combining documentary analysis, contextualized pedagogical activities, field trips, and evaluative records. The students' direct contact with community places and practices fostered the development of identity bonds and redefined their relationship with the territory, encouraging more critical readings of historical permanence and change. The conclusion is that the systematic inclusion of heritage education as a core curriculum contributes to the development of critical competencies, connecting the past to students' trajectories and the territory's social struggles, and reinforces the school's role as a mediator between memory, identity, and citizenship.Keywords: History teaching. Historical consciousness. Cultural heritage. Collective memory. Local identity.
Keywords: history teaching; historical consciousness; cultural heritage; collective memory; local identity